MENGUKUR KESEHATAN KEUANGAN JASA PERHOTELAN DENGAN MODEL ALTMAN, SPRINGATE DAN ZMIJEWSKI - Atun Yulianto (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2014)
Good financial health of the company is the hope of every business that was established to generate good profits for owners, management and employees. Knowing how healthy financial company can be measured by various methods, including using methods developed several experts through various tests before such models Altman, Springate and Zmijewski. The method used is descriptive quantitative. In this research, PT. Hotel Madarine Regency Tbk as sample measured using the three models mentioned above to determine how good the financial health since 2007 to 2011. The intent of this research is to get the prediction probability companies experiencing financial distress in the future. Results of the research found that it, with model equations Altman and Springate financial health of company stated on alert for made possible financial distress will occur in the future. Whereas Model through company's financial health Zmijewski declared having no problems so predictable company will not experience financial distress in the future.